¿Efecto dominó o efecto mariposa? El (distorsionado) concepto de consumidor protegido en el derecho peruano - Cavero Safra, Enrique (2016)
In this article, the author tell us regarding the main function of the consumer protection system, which is to maximize the making good decisions consumption by consumers. Likewise, he tells us about the  information asymmetry and how it should be considered, as well as the inequality between a consumer and a seller. To end, he points out the discussion of whom and why would be considered as consumers as well as the effects of this decision.